Design and synthesis of lipidic organoalkoxysilanes for the self-assembly of liposomal nanohybrid cerasomes with controlled drug release properties - Liang, Xiaolong (2014)
This paper reports the facile design and synthesis of a series of lipidic organoalkoxysilanes with different numbers of triethoxysilane headgroups and hydrophobic alkyl chains linked by glycerol and pentaerythritol for the construction of cerasomes with regulated surface siloxane density and controlled release behavior. It was found that the number of triethoxysilane headgroups affected the properties of the cerasomes for encapsulation efficiency, drug loading capacity, and release behavior. For both water-soluble doxorubicin (DOX) and water-insoluble paclitaxel (PTX), the release rate from the cerasomes decreased as the number of triethoxysilane headgroups increased. The slower release rate from the cerasomes was attributed to the higher density of the siloxane network on the surface of the cerasomes, which blocks the drug release channels. In contrast to the release results with DOX, the introduction of one more hydrophobic alkyl chain into the cerasome-forming lipid resulted in a slower release rate of PTX from the cerasomes due to the formation of a more compact cerasome bilayer. An MTT viability assay showed that all of these drug-loaded cerasomes inhibited proliferation of the HepG2 cancer cell line. The fine tuning of the chemical structure of the cerasome-forming lipids would foster a new strategy to precisely regulate the release rate of drugs from cerasomes.